Process Optimization of Chlorobenzene Production through the Integration of a Distillation Unit and Mixer in Gas–Liquid Benzene Chlorination - Edward Sidhik; Kianaya Raisa; Naufal Ismail Akbar; Nurul Apriturlina; Tibra Sausan Hisanah; Yeremia Cris Natanael Sirait (Journal of Chemical Engineering Research Progress, 2026)
Chlorobenzene is a key intermediate in the synthesis of phenol, aniline, and dichlorodiphenyltrichloroethane (DDT), and is also utilized as a solvent, heat-transfer fluid, and occasionally in dry-cleaning. Given its wide industrial applications, production efficiency is essential for economic viability. This study explores yield enhancement in chlorobenzene manufacture through modifications to the benzene chlorination process. The intensification strategy involved the addition of a distillation column and a mixer unit, while sensitivity analyses were performed using chemical engineering simulation software to assess the influence of operating parameters. The modified process increased chlorobenzene yield from 83% to 98%. Sensitivity analysis revealed that higher benzene feed pressure negatively impacted liquid-phase product yield, whereas a greater benzene-to-chlorine mass flow ratio improved yield by enhancing selectivity toward chlorobenzene formation. These findings demonstrate that process modifications combined with optimized operating conditions can significantly improve chlorobenzene production efficiency. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).